Effects of Scavenging, Entrainment, and Aqueous Chemistry on Peroxides and Formaldehyde in Deep Convective Outflow Over the Central and Southeast United States. Issue 14 (19th July 2018) - Bela, Megan M.; Barth, Mary C.; Toon, Owen Brian; Fried, Alan; Ziegler, Conrad; Cummings, Kristin A.; Li, Yunyao; Pickering, Kenneth E.; Homeyer, Cameron R.; Morrison, Hugh; Yang, Qing; Mecikalski, Retha M.; et al.
Abstract: Deep convective transport of gaseous precursors to ozone (O3 ) and aerosols to the upper troposphere is affected by liquid phase and mixed‐phase scavenging, entrainment of free tropospheric air and aqueous chemistry. The contributions of these processes are examined using aircraft measurements obtained in storm inflow and outflow during the 2012 Deep Convective Clouds and Chemistry (DC3) experiment combined with high‐resolution (d x ≤3 km) WRF‐Chem simulations of a severe storm, an air mass storm, and a mesoscale convective system (MCS). The simulation results for the MCS suggest that formaldehyde (CH2 O) is not retained in ice when cloud water freezes, in agreement with previous studies of the severe storm. By analyzing WRF‐Chem trajectories, the effects of scavenging, entrainment, and aqueous chemistry on outflow mixing ratios of CH2 O, methyl hydroperoxide (CH3 OOH), and hydrogen peroxide (H2 O2 ) are quantified. Liquid phase microphysical scavenging was the dominant process reducing CH2 O and H2 O2 outflow mixing ratios in all three storms. Aqueous chemistry did not significantly affect outflow mixing ratios of all three species. In the severe storm and MCS, the higher than expected reductions in CH3 OOH mixing ratios in the storm cores were primarily due to entrainment of low‐background CH3 OOH. In the air mass storm, lower CH3 OOH and H2 O2 scavenging efficiencies (SEs) than in the MCS were partly due to entrainment of higher background CH3 OOH and H2 O2 . Overestimated rain and hail production in WRF‐Chem reduces the confidence in ice retention fraction values determined for the peroxides and CH2 O. Key Points: Methyl hydroperoxide mixing ratios are decreased mainly by entrainment and liquid phase and mixed‐phase scavenging Hydrogen peroxide and formaldehyde mixing ratios affected more by liquid phase scavenging than by entrainment or aqueous chemistry Overestimated rain/hail production in WRF‐Chem reduces confidence in ice retention fraction values determined for peroxides and formaldehyde